Alef, mem, tau : kabbalistic musings on time, truth, and death - Wolfson, Elliot R. (Berkeley : University of California Press, 2006)
This highly original, provocative, and poetic work explores the nexus of time, truth, and death in the symbolic world of medieval kabbalah.
Thinking time/hermeneutic suppositions -- Linear circularity/(a)temporal poetics -- Before alef/where beginnings end -- Within mem/returning forward -- After tau/where endings begin -- Conclusion.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Time -- Philosophy; Time -- Religious aspects -- Judaism; Cabala -- History; Temps -- Philosophie; Kabbale -- Histoire; RELIGION -- Judaism -- Kabbalah & Mysticism; RELIGION -- Judaism -- General; Cabala; Time -- Philosophy; Time -- Religious aspects -- Judaism; Humaniora -- Religionsvidenskab; Humaniora -- Jødisk kultur og historie; History